Generation of an induced pluripotent stem cell line (ZSPHARi002-A) from a patient with autosomal dominant polycystic kidney disease carrying a heterozygous PKD1 mutation - Yeye Zhang; Ye Chen; Jun Fan; Guangzhao Lu; Qianzhou Lv; Donghui Lao; Xiaoyu Li (Stem Cell Research)
Autosomal dominant polycystic kidney disease (ADPKD), a single-gene-inherited kidney disease, is a common cause of end-stage kidney disease (ESKD). The PKD1 gene mutation is the most common cause of ADPKD, accounting for approximately 78% of cases. ADPKD is characterized by the scattered distribution of multiple cysts in the renal parenchyma, ultimately leading to ESKD. We collected peripheral blood mononuclear cells from a patient with ADPKD who carries a heterozygous PKD1 mutation and reprogrammed them into induced pluripotent stem cells (iPSCs). iPSC lines can provide a valuable resource for studying the pathogenesis of ADPKD and for drug screening purposes.